A new subgenus Oculogaster subgen. n. for viviparous representatives of Procloeon s. l., with discussion about status of the generic name Austrocloeon Barnard 1932 and the species name africanum Esben-Petersen 1913 [Cloeon] (Ephemeroptera, Baetidae) - Kluge, Nikita J. (Zootaxa, 2016)
A new subgenus Oculogaster subgen. n. is established in the genus Procloeon Bengtsson 1915. It is characterized by viviparity and constant presence of one vein in pterostigma. Widely distributed African species Procloeon (Oculogaster) cylindroculum Kimmins 1956 is redescribed based on male and female imagoes reared from larvae in Zambia and Uganda. A new species Procloeon (Oculogaster) album sp. n. is described based on reliably associated larvae, subimagoes and imagoes of both sexes from Thailand. Status of the generic name Austrocloeon Barnard 1932 and the species name Cloeon africanum Esben-Petersen 1913 are discussed, and the nominal species C. africanum is fixed as the type species of the genus-group name Austrocloeon; according to this type fixation, the binomen Austrocloeon africanum belongs to a species of the subfamily Rhithrocloeoninae.